2001
DOI: 10.2116/analsci.17.1257
|View full text |Cite
|
Sign up to set email alerts
|

Flow-injection Chemiluminometric Determination of Some Thioxanthene Derivatives in Pharmaceutical Formulations and Biological Fluids Using the [Ru(dipy)32+]-Ce(IV) System

Abstract: The thioxanthene class of drugs is effective in the systematic treatment of psychoses. They are most appropriately used in the therapy of schizophrenia, organic psychoses and other idiopathic psychotic illnesses. 1 However, these drugs have other clinically useful properties, including anti-emetic, antinausea and antihistamine effects, and the ability to potentiate analgesics, sedatives and general anaesthetic actions. 1 Several methods have been reported for the determination of thioxanthenes either in pure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
(13 reference statements)
0
10
1
Order By: Relevance
“…Moreover, sensitivity is not good enough for the determination of QN residues. In the present work, we found that QNs could strongly enhance the CL of the Ce(SO 4 ) 2 -Ru(bpy) 3 2+ -HNO 3 system, the enhanced CL signal was much stronger than the Ce(SO 4 ) 2 -Ru(bpy) 3 2+ system reported by Aly et al [27] using flow-injection CL method, and the detection limits were lower than that of reported. To our knowledge, there is no report using HPLC-CL to detect QN residues.…”
Section: Introductioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Moreover, sensitivity is not good enough for the determination of QN residues. In the present work, we found that QNs could strongly enhance the CL of the Ce(SO 4 ) 2 -Ru(bpy) 3 2+ -HNO 3 system, the enhanced CL signal was much stronger than the Ce(SO 4 ) 2 -Ru(bpy) 3 2+ system reported by Aly et al [27] using flow-injection CL method, and the detection limits were lower than that of reported. To our knowledge, there is no report using HPLC-CL to detect QN residues.…”
Section: Introductioncontrasting
confidence: 51%
“…QNs were observed to enhance the net CL intensity in Ce(IV)-Ru(bpy) 3 2+ system [27]. We found that when HNO 3 was added to the system, the enhanced CL signals of QNs were increased sharply.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations